(untitled) (Management Dynamics, 2024)
This study provides the first comprehensive econometric assessment of Nepal Rastra Bank’s Interest Rate Corridor (IRC) effectiveness during the post-COVID period (2020-2023). Using Vector Error Correction Models, GARCH volatility analysis, and difference-in-differences methodology, we examine corridor performance across rate anchoring, volatility reduction, and transmission mechanism enhancement. Results indicate mixed effectiveness: while rate anchoring declined moderately during crisis periods (from 89% to 82%), substantial improvements occurred in transmission speed (43% faster) and pass-through completeness (a 63% increase). The IRC framework successfully accommodated extraordinary policy responses while maintaining core transmission mechanisms. Policy recommendations include an optimal corridor width of 300-350 basis points and enhanced accessibility to standing facilities. Findings contribute to the literature on crisis-period monetary policy effectiveness in developing economies.